PEMBENTUKAN KATA DALAM KOMIK HANAZAKARI NO KIMITACHI HE IKEMEN PARADISE VOLUME 1 - Suliyanto, Eirene Putri (Jurnal Ilmiah Mahasiswa FIB, 2013)
In studying any kind of language including Japanese, new beginners will observe all the basic and general thing, but when they to learn more they will find that the basic or general vocabularies they have learnt before are different in writing or  pronounciation and it is caused by word formation. The goals of this study are to knowing (1) the kind of word classes changed in comic Hanazakari no Kimitachi he Ikemen Paradise Vol. 1, (2) the changings of words found in comic Hanazakari no Kimitachi he Ikemen Paradise Vol. 1, and (3) the changing characteristic of the words found in comicHanazakari no Kimitachi he Ikemen Paradise Vol. 1.This study uses descriptive approach. Descriptive study in textual analysis is applied in this study to analyze conversation of one of the main characters called Sano Izumi through the script of Hanazakari no Kimitachi he Ikemen Paradise Vol. 1 comic.This study reveals that (1) the word classes changed in the comic are adverb, adjective, nomina, pronomina, shuushikei, and verb, (2) the words changed in the comic undergo one and two changing processes, and (3) there are two characteristics of the changed words, which are the same ending and the frequency of the processes and the paterns that appear often.The writer suggest Japanese Department students study more about word formation by focusing on one or some changing processes and using many resources. Also the writer considers that there is a need to introduce word formation to the Japanese new learners.